1991
DOI: 10.1007/bf00194285
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the activation state of sucrose-phosphate synthase and the rate of CO2 assimilation in spinach leaves

Abstract: The relationship between the gas-exchange characteristics of spinach (Spinacia oleracea L.) leaves and the activation state of sucrose-phosphate synthase was examined at different intercellular partial pressures of CO2 at two different photon flux densities. There was a strong positive correlation between the activation state of sucrose-phosphate synthase and the assimilation rate. The relationship was the same at both photon flux densities, indicating that the activation state of the enzyme is determined by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…Because direct product inhibition by sucrose-6-phosphate does not appear to play an important role in the regulation of SPS (Krause and Stitt 1992), it appears that SPS activity is a major factor in determining flux through the pathway of sucrose biosynthesis (Galtier et al 1993). Our results support the contention of a strong positive correlation between CO2 assimilation rate and SPS activity (Galtier et al 1993;Hurry et al 1994b) and SPS activation state (Battistelli et al 1991).…”
Section: Discussionsupporting
confidence: 89%
“…Because direct product inhibition by sucrose-6-phosphate does not appear to play an important role in the regulation of SPS (Krause and Stitt 1992), it appears that SPS activity is a major factor in determining flux through the pathway of sucrose biosynthesis (Galtier et al 1993). Our results support the contention of a strong positive correlation between CO2 assimilation rate and SPS activity (Galtier et al 1993;Hurry et al 1994b) and SPS activation state (Battistelli et al 1991).…”
Section: Discussionsupporting
confidence: 89%
“…SPS activity has been shown to be a determinant of the synthetic rate of Suc in leaves (Battistelli et al, 1991;Winter and Huber, 2000;Baxter et al, 2003;Haigler et al, 2007). Interestingly, two lines of evidence from our study suggest a possible role of SnRK2.6 in increasing SPS activity.…”
Section: Snrk26 Imparts Carbon Source and Sink Strength Through Regusupporting
confidence: 58%
“…6 and 7). Because the capacity for Suc synthesis in the cytosol limits the maximal rates of photosynthesis by restricting the recycling rate of inorganic phosphate to support electron transport and carbon fixation in the chloroplast (Stitt, 1986), increasing Suc synthesis has a positive impact on photosynthetic rate (Ho and Thornley, 1978;Stitt, 1986;Battistelli et al, 1991;Baxter et al, 2003). In addition, it has been shown that the rate of Suc synthesis is also positively correlated with the rate of Suc export from leaves (Ho and Thornley, 1978;Rocher et al, 1989;Baxter et al, 2003;Park et al, 2007).…”
Section: Snrk26 Imparts Carbon Source and Sink Strength Through Regumentioning
confidence: 99%
“…Activity of SPS is closely correlated with the capacity of a leaf to synthesize sucrose (Harbron et aL, 1981;Huber & Israel, 1982) and is dependent on the assimilation rate (Battistelli, Adcock & Leegood, 1991); covalent tnodification alone could account for our results. Additionally, substances known to inhibit SPS may accumulate in diseased leaves.…”
Section: Discussionsupporting
confidence: 57%